THE EFFECT OF PHYSICAL ACTIVITY OF DIFFERENT INTENSITY ON THE FEMALE ORGANISM - Arabboyev Qahramon Tohirjonovich; Zokirova Feruza Mukhtorjon kizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The evolutionarily acceptable amount of physical activity is different for men and women. This article describes the influence of the most effective and optimal physical activity on the body of female students involved in physical exercise and sports.